Osmotic Demyelination Syndrome due to Rhabdomyolysis and Hyperosmolar Hyperglycemic Syndrome following Cardiogenic Shock - Kosuke Katano; Nozomi Fuse; Yoshitaka Asano; Kimihiro Osada; Akira Miyabe; Ryuma Ishihara; Atsushi Tosaka; Yuriko Satoh; Masako Maeda; Taisuke Mizumura; Akio Oshima; Toshitake Tamamura; et al. (Case Reports in Critical Care)
Osmotic demyelination syndrome (ODS) is a relatively rare disease that causes rapid demyelination, resulting in pontine and central nervous system damage with various symptoms, including impaired consciousness. It often occurs when hyponatremia is rapidly corrected. However, it can also occur when a normonatremic patient suddenly develops hypernatremia. A 51-year-old man developed cardiogenic shock with impaired consciousness, hyperCKemia, hypernatremia, and hyperglycemia. Osmotic demyelination syndrome secondary to rhabdomyolysis and hyperosmolar hyperglycemic syndrome was suspected. The patient’s fluid volume decreased because of osmotic diuresis caused by hyperglycemia, and the blood sodium level increased rapidly. The latter resulted in ODS, which in turn resulted in a prolonged disturbance of consciousness, from which he has not yet recovered. ODS has been reported as a serious complication of rapid correction of hyponatremia, although it also occurs when normonatremia leads to hypernatremia. This disease is difficult to diagnose, as magnetic resonance imaging (MRI) of the brain is often unremarkable several weeks after its onset. This case of ODS occurred when normonatremia led to hypernatremia, as a result of rhabdomyolysis and hyperosmolar hyperglycemic syndrome. Diagnosis was made based on the MRI brain findings.